Whole-genome sequencing analysis of Salmonella enterica serotype Enteritidis isolated from poultry sources in Mongolia - Song, Seung-un; La, Tae-Min; Kim, Taesoo; Kim, Junyoung; Shin, Eunkyung; Temuujin, Uyangaa; Hyeon, Ji-Yeon; Lee, Dong-Hun; Lee, Sang-Won (Frontiers in Veterinary Science, 2025)
Salmonella enterica serotype Enteritidis (S. Enteritidis) is a leading foodborne pathogen associated with poultry products, and the emergence of antimicrobial resistance (AMR) in this serotype poses a growing public health concern, particularly in regions with increasing poultry trade. Between April and June 2024, we collected 114 poultry meat samples (Mongolian domestic and Chinese imported) from retail markets in Mongolia and isolated 45 S. Enteritidis strains. Antimicrobial susceptibility testing revealed high resistance rates to nalidixic acid (100%), ampicillin (93.3%), and streptomycin (88.9%). Whole-genome sequencing (WGS) identified major resistance genes, including aac(6′)-Iaa, aph(3″)-Ib, blaTEM-1B, and sul2. Mongolian domestic isolates additionally harbored extended-spectrum β-lactamase (ESBL) blaCTX-M-14 and plasmid-mediated quinolone resistance (PMQR) qnrS1, both of which are clinically significant. Plasmid replicon typing revealed IncF as the most prevalent type across isolates, while IncI1- α was predominantly found in multidrug-resistant (MDR) domestic strains. Phylogenetic analysis using whole-genome SNPs (wgSNPs) demonstrated that domestic and imported isolates clustered separately, indicating that Chinese S. Enteritidis strains have not yet been introduced into Mongolia’s domestic poultry industry. This study represents the first comprehensive analysis of prevalence and resistance mechanisms of S. Enteritidis in Mongolia poultry production. The findings underscore the necessity of continuous surveillance and the implementation of effective antibiotic stewardship in the poultry production sector.